PARIWISATA HALAL BALI: STUDI KASUS PENERAPAN PARIWISATA HALAL OLEH NUSANTARA TOUR & TRAVEL TAHUN 2024 - Supardi, Supardi (Universitas Mathla’ul Anwar Banten, 2025)
Halal tourism has become a trending topic in the last decade, so it is not surprising that everyone involved in the world of tourism participates in studying, understanding, alluding to, supporting, opposing and even provoking positively and negatively towards this halal tourism. Bali carries tourism that emphasizes culture. Nature tourism in Bali is known as cultural tourism and is also referred to as the local wisdom of the Balinese people and is philosophically based on Hindu teachings (Darmawan, 2023; Risfandini, 2019). Therefore, there must be a role for stakeholders in efforts to develop halal tourism in Bali. This is because halal tourism is universal, not bound by a particular form that can prevent the island of the gods 'Bali' from developing halal tourism. Moreover, the prospects for the halal tourism business are very large because halal is not just about religion, but has become a choice, opportunity, and lifestyle. The purpose of this study is to find out Halal Tourism in Bali (Case Study of the Implementation of Halal Tourism by PT. Nusantara tour & travel)